2014
DOI: 10.1161/hypertensionaha.113.03353
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet Reduces 24-Hour Ambulatory Blood Pressure, Blood Glucose, and Lipids

Abstract: H igh blood pressure (BP) is a major risk factor for coronary heart disease, congestive heart failure, stroke, and renal disease 1 and as such is the leading cause of preventable deaths worldwide. 2 In 2000, 26.4% of the adult world population (972 million) had hypertension, defined as BP ≥140/90 mm Hg or current use of antihypertensive medication, and 29.2% were projected to be hypertensive by 2025. 3 The prevalence of hypertension increases with age, with the estimated lifetime risk for elderly subjects re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(121 citation statements)
references
References 31 publications
3
97
1
7
Order By: Relevance
“…Ambulatory blood pressure has been shown to eliminate "white coat hypertension" and has increased precision over office BP [60]. Repeated measurements of ambulatory blood pressure provide an even more accurate indication of usual BP than a single 24hr measurement [61]. However, automated office BP measurement is recommended for use in primary care settings as it has been shown to be comparable with awake ambulatory BP [62], and was thus deemed appropriate in this research context.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory blood pressure has been shown to eliminate "white coat hypertension" and has increased precision over office BP [60]. Repeated measurements of ambulatory blood pressure provide an even more accurate indication of usual BP than a single 24hr measurement [61]. However, automated office BP measurement is recommended for use in primary care settings as it has been shown to be comparable with awake ambulatory BP [62], and was thus deemed appropriate in this research context.…”
Section: Discussionmentioning
confidence: 99%
“…One of the arrangements set out for this improvement was the reduction of oxidative stress and inflammation. [53][54][55][56][57] Among these studies, Mitjavila et al 58 observed a decrease of some markers of oxidative stress after one year of dietary intervention. In this same study, subjects with MetS who consumed the Mediterranean diet were compared to a group that consumed a diet with only low levels of fat.…”
Section: Biomarkers Of Oxidative Stressmentioning
confidence: 99%
“…[42][43][44][45][46][47][48][49][50][51][52][53] Mediterranean Diet 975 lower total cholesterol/HDL-C ratios compared with the low(er)-fat group (À0.38 and À0.26, respectively). In addition, the Mediterranean diet with nuts reduced fasting glucose (À5.4 mg/dL), SBP (À7.1 mm Hg), DBP (À2.6 mm Hg), and TG concentrations (À13 mg/dL) relative to the low(er)-fat diet.…”
Section: Mediterranean Diet: Overview and Evidence Basementioning
confidence: 99%
“…44 However, in a subsequent analysis of a larger nondiabetic population, only the Mediterranean diet supplemented with EVOO reduced the risk of new-onset type 2 diabetes. 45 Additional follow-up studies reported reductions in carotid intima-media thickness, 46,47 apolipoproteins, 48 very low-density lipoprotein (VLDL) cholesterol, 49 inflammatory biomarkers, 50 and improvements in DBP, 51 ambulatory blood pressure, 52 and heart failure biomarkers. 53 It is interesting that supplementation with nuts versus EVOO elicited beneficial effects on different CVD risk factors, without a clear trend indicating whether one dietary pattern was more effective.…”
Section: Mediterranean Diet: Overview and Evidence Basementioning
confidence: 99%